If a + b + c = 2s, then the value of (s - a)2 + (s - b)2 + (s - c)2 + s2 will be-

  • 1s2 - a2 - b2 - c2
  • 2s2 + a2 + b2 + c2
  • 3a2 + b2 + c2
  • 44s2 - a2 - b2 - c2
Answer:- 1
Explanation:-

Solution:
(sa)2+(sb)2+(sc)2+s2=(s2+a22sa)+(s2+b22sb)+(s2+c22sc)+s2=4s2+(a2+b2+c2)2s(a+b+c)=(2s)2+(a2+b2+c2)(a+b+c)(a+b+c)=(a+b+c)2+(a2+b2+c2)(a+b+c)2=a2+b2+c2

Post your Comments

Your comments will be displayed only after manual approval.

", "dateCreated": "7/24/2019 10:09:12 AM", "author": { "@type": "Person", "name": "Nitin Sir" } }, "suggestedAnswer": { "@type": "Answer", "text": "
Solution:
(sa)2+(sb)2+(sc)2+s2=(s2+a22sa)+(s2+b22sb)+(s2+c22sc)+s2=4s2+(a2+b2+c2)2s(a+b+c)=(2s)2+(a2+b2+c2)(a+b+c)(a+b+c)=(a+b+c)2+(a2+b2+c2)(a+b+c)2=a2+b2+c2
", "dateCreated": "7/24/2019 10:09:12 AM" } }
Test
Classes
E-Book